FAKTOR RISIKO OBESITAS SENTRAL PADA ORANG DEWASA DI DKI JAKARTA: Analisis Lanjut Data RISKESDAS 2007 - Sugianti, Elya; ., Hardinsyah; Afriansyah, Nurfi (PERSATUAN AHLI GIZI INDONESIA, 2009)
RISK FACTORS OF CENTRAL OBESITY AMONG ADULTS IN DKI JAKARTAObesity is now considered as a major public health problem, afflicting both developed anddeveloping countries including Indonesia. Recently, central obesity, measured by waistcircumference, draw a greater attention than overall obesity, measured by body mass index, sincemore risks have been proved to be associated with central obesity. The objective of the study is toanalyzed risk factors associated with central obesity in DKI Jakarta. The study used secondary dataof Basic Health Research (RISKESDAS) conducted in 2007 in DKI Jakarta. A Total of 11805 men andwomen age 15 year old or above excluding pregnant women were used for the analyses. Logisticregression analyses were used to measure the association between central obesity and existingvariables in the data on the characteristic of subject. The result showed that significant risk factorsassociated with central obesity are age 35 year, sex (women), marital status (married), education(high school), occupation (entrepreneur/ tradesman/ services/ housewife), per capita income(quintile-5), fatty foods and mental disorders. Among those risk factors, sex (women) is the mostdeterminant risk factor.Keywords: central obesity, risk factors, BasicHealth Research (RISKESDAS)